Public Speaking Training in Building Self-Confidence as Optimal Preparation for the World of Work for Students of SMK Budi Asih, Jakarta - Yudha Pradhana; Vivitri Endah Andriani; Mira Adita Widianti; Firyal Nailah Khansa; Dinar Kadarsih; Albert Deniel Sitorus (Ponpes As-Salafiyyah Asy-Syafi'iyyah, 2025)
SMK Budi Asih, one of the secondary education institutions in Jakart, is responsible for producing graduates with technical ando good communication skills. Through speaking skills, students will be able to express ideas, thoughts, and information in the right way in public and not cause misunderstandings as optimal preparation for the world of work. This training is designed to improve students' speaking skills, self-expression, and effective communication so that they can face competitive challenges in the increasingly complex world of work. Involving interactive training methods, this activity not only focuses on the technical aspects of public speaking, but also strengthens the psychological aspects to overcome the fear of speaking in public. The results of this training can positively impact increasing self-confidence and preparing SMK Budi Asih students to face challenges in the dynamic world of work. The success of this training is expected to be measured through participant evaluation and monitoring the development of public speaking skills and increasing students' self-confidence.